2022
DOI: 10.3889/oamjms.2022.8187
|View full text |Cite
|
Sign up to set email alerts
|

The Dominant Factors Affecting the Low Participation of Young Women Ever Married in the Family Planning Program (KB) in Papua Province (2017 IDHS Data Analysis)

Abstract: BACKGROUND: Participation in family planning (FP) among young women who have ever married is the spearhead in reducing the Total Fertility Rate in Papua Province. However, the percentage of FP use in Papua Province in Papua Province is still very low, at 74.88%. This study looks at the dominant factors that influence the low participation of ever married young women in FP programs in Papua Province. METHODS: This study is a cross-sectional study using data from the 2017 Indonesian Health Demographic Survey, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…A similar study related to unmet needs of family planning found contraception, maternal age, mother's education, number of children's ownership, history of child death, wealth index, province of residence, knowledge about contraceptive use, and ever used anything to delay getting pregnant were determine the unmet needs of contraceptive use (Hastuti et al, 2022). The specific study focused on the Papua region (Eastern Indonesia) and found that the factors associated with low participation in family planning methods among young married women were household expenditure and age at first sexual intercourse (Rahmadani et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…A similar study related to unmet needs of family planning found contraception, maternal age, mother's education, number of children's ownership, history of child death, wealth index, province of residence, knowledge about contraceptive use, and ever used anything to delay getting pregnant were determine the unmet needs of contraceptive use (Hastuti et al, 2022). The specific study focused on the Papua region (Eastern Indonesia) and found that the factors associated with low participation in family planning methods among young married women were household expenditure and age at first sexual intercourse (Rahmadani et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…National Population and FP Board is responsible for demand creation of FP services while Ministry of Health is responsible for its supply. So far, several studies have described the success of FP Program only seen from the public's point of view [2], [3], [4], [5], [6], [7], [8] and the roles of healthcare staff, especially in terms of supply/contraceptive tool supply. Those studies included contraceptive guideline [9], contraceptive financing policies [10], contraceptive usage failure policies [11], education and training for healthcare staff in administering contraceptive services [12], and monitoring and evaluation of FP program for healthcare staff [13].…”
Section: Introductionmentioning
confidence: 99%